Political Motives in the „Medea" of Euripides - Kazlauskas, Benediktas (Literatūra, 1967)
The presence of political motives in the "Medea" of Euripides has already been indicated by L. Sechan, E. Delebecque, Otkupschikov. Dwelling on this problem, the former two overestimate the political element of this tragedy, especially in those places where Medea's enemies are described. Moreover, they do not see the difference between the enemies of Medea's family and the Corinthians, who are considered her enemies from the political point of view.This double understanding and the differentiation of Medea's enemies in the tragedy is inevitable. Otherwise, her Corinthian enemies, who are political rivals of the Athenians, at the same time are regarded as enemies of her family. This leads to overestimation of the political and military motives in the tragedy and belittles the psychological problem of the family. Admitting that Medea's personal enemies should be regarded as her enemies from the political point of view, including King Creon's family and relatives, one neglects Euripides' striving to conciliate the Corinthians and the Athenians. In case the common notion "Corinthians" was prevailing in the tragedy over Creon's family and its relations with that of Medea, we should have to face the conclusion that Euripides was instigating the Athenians to a war against the Corinthians. Hence Medea's flight to Athens should acquire political meaning, and her reception in Athens should be regarded as a crime. Here one more conclusion might be drawn, i.e., that Euripides was for a war against Corinth.The Corinthians in the "Medea" of Euripides are her political enemies only in some places of the tragedy. "Enemies" here are understood mostly as enemies of her family. The enemies of Medea's family are considered to be Creon's family and his relatives in the following lines: 94-95, 163, 166, 734-735, 743-744, 794-798, 809-810, 920-921, 953-957, 1040-1050, 1059-1061, 1236-1239, 1301-1305. Medea's enemies from the political point of view are described in the following lines: 750-751. Especially a very evident political allusion is hidden in lines 780-783. In Greek, the idea of it might be expressed by the words: ἱστορεῖ ἐν χλωρῷ. Political hints are perceived in lines 1378-1380, where Medea depicts the burial of her children.Introducing the motive of her children's murder, Euripides probably wished to take the blame off the Corinthians and to create a favourable atmosphere for negotiations and peace on the eve of the Peloponnesian War. The political motive to alleviate the relations between Athens and Corinth can be traced in Creon's behaviour towards Medea—making a concession and allowing her to stay one more day in Corinth.The tendency to normalize the relation of the opposing forces can hardly be traced in other places of the tragedy. Animosity against the Corinthians is evident in lines 404-406. On the other hand, in lines 439-440, the hints are condemning not them, but the Athenians for their hostility towards the foreigners. Though in the scene with Aegeus one can trace some peacefulness towards the enemies of Medea and Corinth, even here there are some hostile words against Creon and the Corinthians (lines 695, 699). Besides, the patronizing attitude towards Medea, receiving her in Athens, had to make a negative influence on the Athenians who opposed the Corinthians. These contradictory thoughts to blame both the Corinthians and the Athenians reveal the nature of Euripides' creative method and his political wisdom.
Keywords: -